The Influence Of The Project-Based Learning Model Using Loose Parts Media And Learning Motivation On Student Creativity In Group B, Insan Cendekia TK - Chusnul Chotimah; Nurmida Catherine Sitompul (Departement of Mathematics Education, 2024)
The purpose of this research is to find out: (1) the difference in learning outcomes between the use of Project-Based Learning Using Loose Parts Media and conventional methods on the Creativity of group B Kindergarten Insan Scholar, (2) the difference high learning motivation and low learning motivation on the creativity of group B of the Insan Scholar Kindergarten, and (3) the interaction between learning model and learning motivation on the creativity of group B of the Insan Scholar Kindergarten, in this case motivation as a moderator variable really supports the strong relationship between the independent variable and the dependent variable. This experimental research was carried out using a 2x2 factorial design. The subjects in this research were class VIII students consisting of four classes with 110 group B students at the Insan Scholar Kindergarten. The subjects that were the focus of the experiment were taken at random, namely group B of the Insan Scholar Kindergarten. This research hypothesis was tested using the Analysis of Variant (Anova) statistical test. The calculation results show that: Based on the results of hypothesis testing and the discussion in chapter V, it can be concluded as follows: (1) There is a difference in the influence of using Project-Based Learning Using Loose Parts Media and conventional methods on the Creativity of group B of Kindergarten Scholars, namely students who using Project-Based Learning Using Loose Parts Media has better creativity than students who use conventional methods, (2) There is a difference in the influence of high learning motivation and low learning motivation on the creativity of group B of Kindergarten Insan Intellectuals, namely students with high learning motivation are better creativity than students with low learning motivation, and (3) There is an interaction effect between the learning model and learning motivation on the creativity of group B of the Insan Scholar Kindergarten, in this case motivation as a moderator variable really supports a strong relationship between the independent variable and the dependent variable. The Effect of Using Project-Based Learning Using Loose Parts Media with high motivation can increase creativity